1997
DOI: 10.1021/la970324+
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of a Chemisorbed Peptide Film Using Beads Activated with Covalently Bound Chymotrypsin

Abstract: Silica and polyacrylamide microspheres were modified with chemisorbed chymotrypsin and used to enzymatically hydrolyze a peptide thin film which was covalently bound to a flat silica surface. Chymotrypsin was covalently cross-linked to 500 nm silica spherical beads and 30-50 µm polyacrylamide spherical beads and shown to be enzymatically active against thin films of a fluorescent peptide, succinyl-ala-ala-phe-7-amido-4-methylcoumarin (SAAP-AMC), and an unlabeled peptide, t-BOC-phe. SAAP-AMC and t-BOCphe were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Most of these existing examples focus on the use of enzymes to produce surface patterns. Enzymes were immobilized on AFM tips, 23-28 stamps 29,30 or silica beads 31 to create patterns on surfaces modified with DNA, 28,29 peptides, 23,31 phospholipids 25 or polymers. 26,27,30 Examples of enzymes used include serine protease, 23 proteinase K, 26 trypsin, 30 chymotrypsin, 31 horseradish peroxidase, 27 phospholipase A 2 , 25 DNAse I 28 and exonuclease I.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these existing examples focus on the use of enzymes to produce surface patterns. Enzymes were immobilized on AFM tips, 23-28 stamps 29,30 or silica beads 31 to create patterns on surfaces modified with DNA, 28,29 peptides, 23,31 phospholipids 25 or polymers. 26,27,30 Examples of enzymes used include serine protease, 23 proteinase K, 26 trypsin, 30 chymotrypsin, 31 horseradish peroxidase, 27 phospholipase A 2 , 25 DNAse I 28 and exonuclease I.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,10 Chemisorption of biomolecules does not suffer from the aforementioned disadvantages and provides a durable linkage between the molecule and the surface. 11 For example, the detection of enterotoxin B by a surface-bound antibody was dependent on covalent grafting of the antibody to silica surfaces. Antibodies that were physisorbed were not well-structured and acted like insulators interfering with capacitancebased detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of proteins, peptides, or enzymes on solid supports such as silica may be obtained by simply incubating the surface with the desired organic molecules. However, such a crude strategy results in surfaces which suffer from denaturation, leaching and inconsistency in the activity of the adsorbed layer, and these problems lead to difficulties in both understanding structure−function relationships and accurate surface characterization of the adsorbed layer. ,, Chemisorption of biomolecules does not suffer from the aforementioned disadvantages and provides a durable linkage between the molecule and the surface . For example, the detection of enterotoxin B by a surface-bound antibody was dependent on covalent grafting of the antibody to silica surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction for chymotrypsin suggests that the enzyme may have cleaved the bond on the carboxylic acid side of Phe, an observation previously reported by Turner et al using SIMS and XPS in a similar system, although this work used chymotrypsin covalently bound to silica beads. 19 For Fmoc-Phe-Gly, chymotrypsin . XPS C 1s core level spectra for both Fmoc-dipeptide surfaces following incubation with both enzymes and the water controls using Method 3.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work by Turner et al demonstrated that enzymatic modification of surface-tethered molecules is possible, in principle, by the cleavage of surface-bound phosphate esters by a lipase; however, it was observed that non-specific adsorption of protein molecules to the surface limited the effectiveness of this system 18. This problem was solved by using enzymes (chymotrypsin) covalently bound to silica beads,19 a method that both eliminated enzyme adsorption to the surface and allowed for enzyme recovery. Yeo and Mrksich have shown that polyethylene glycol (PEG) surfaces modified with 4-hydroxyphenyl valerate could be used to enzymatically switch a redox-inactive surface to a redox-active surface by de-acylation 20.…”
Section: Introductionmentioning
confidence: 99%